Prevention of Incident Hypertension in Patients With Obstructive Sleep Apnea Treated With Uvulopalatopharyngoplasty or Continuous Positive Airway Pressure: A Cohort Study - Lin, Yi-Chih; Chen, Chun-Tien; Chao, Pin-Zhir; Chen, Po-Yueh; Liu, Wen-Te; Tsao, Sheng-Teng; Lin, Sheng-Feng; Bai, Chyi-Huey (Frontiers in Surgery, 2022)
Objectives: To determine whether treatment with uvulopalatopharyngoplasty (UPPP) or continuous positive airway pressure (CPAP) in patients with obstructive sleep apnea (OSA) prevents hypertension, compared to those not receiving any treatment. Methods: A retrospective cohort study was conducted among 413 patients with OSA (age ≥35 years) at the Shuang Ho Hospital between 2009 and 2016. The patients were divided into three groups: UPPP, CPAP, and non-treatment groups. Data about the personal characteristics, history of comorbidities, and polysomnography(PSG) reports were collected at baseline. A Cox model with inverse probability of treatment weighting was used to adjust for confounders and baseline diversity. Results: After multivariate adjustment and weighting for incident hypertension, patients in both the CPAP and UPPP groups showed a significant preventive effect on hypertension than in the non-treatment group. Moreover, patients in the CPAP group had lower event rates than those in the UPPP group. Conclusion: UPPP can prevent the development of new-onset hypertension in patients with OSA. CPAP had a better preventive effect than UPPP. UPPP might be a good alternative for reducing the risk of the onset of hypertension when compliance to CPAP is poor.